Effects of testosterone and 17β-estradiol on osteogenic and adipogenic differentiation capacity of human bone-derived mesenchymal stromal cells of postmenopausal women - Kristina Glenske; Gerhard Schuler; Stefan Arnhold; Mohamed I. Elashry; Alena-Svenja Wagner; Mike Barbeck; Elena Neumann; Ulf Müller-Ladner; Reinhard Schnettler; Sabine Wenisch (Bone Reports, 2019)
Progressive bone loss is a predominant symptom of aging and osteoporosis. Therefore, the effects of sex steroids (i.e. testosterone and 17β-estradiol) on the differentiation capacity of human bone-derived mesenchymal stromal cells (hMSCs), as progenitors of osteoblasts and adipocytes, are of particular interest. The objectives of the present study were, thus, to elucidate whether bone-derived hMSCs of postmenopausal women produce aromatase (CYP19A1) and, whether they modulate their differentiation behaviour in response to testosterone and 17β-estradiol (E2), in relation to their steroid receptor expression. Supplementation of testosterone resulted in a considerable formation of E2 under osteogenic and adipogenic culture conditions, whereas E2 synthesis remained minimal in the cells cultured in basal medium. Concomitant with high aromatase expression and 17β-estradiol formation of the cells cultured in osteogenic medium supplemented with testosterone, a distinct promotion of late-stage osteogenesis was found, as shown by significant matrix mineralization and a notable increase in osteogenic markers. These effects were abrogated by the aromatase inhibitor anastrozole. Under adipogenic conditions, testosterone reduced the occurrence of lipid droplets and led to a decrease in PPARγ and AR expression, independent of anastrozole. Regardless of the culture conditions, ERα was detectable whilst ERβ was not. In conclusion, aromatase activity is limited to differentiated hMSCs and the resulting 17β-estradiol enhances late osteogenic differentiation stages via ERα. Adipogenic differentiation, on the other hand, is reduced by both sex steroids: testosterone via AR and 17β-estradiol. Keywords: MSCs, Testosterone, 17β-estradiol, Osteogenic differentiation, Adipogenic differentiation, Aromatase activity